Agroforestry in crops systems and its influence on the chemical fertility of soils in semi-arid regions: Case of the Dahra foothills (North-West, Algeria) - Amina, Hamadi; Mohamed, Larid; Calero, José Alfonso Gómez; Habib, Ouabel (Journal of Agriculture and Applied Biology, 2025)
To guarantee a stable offer and healthy food, the new techniques of maintaining and improving the natural production capacity of agri-cultural land must take appropriate measures for each environ-ment. However, the identification and the valorization of all local dynamics of production systems must ensure the conservation of agricultural land fertility and butter fertilizer management. This study aims to evaluate the physico-chemical quality of soils in the north-western foothills of Dahra. After a bioclimatic overview of the study area, out of the fourteen studied stations, four of the most practiced farming systems (agroforestry, non-irrigated tree crop cultivation, annual field cropping and fallow cultivation) were compared based on analyses of various indicators related to the physico-chemical properties of soils used in the literature concerning soil chemical fertility. Indeed, the studied soils ex-hibit a clay-loam and sandy-loam textures, a slightly acidic pH, and an organ-ic matter content that requires improvement for more active biological ac-tivity. To optimize soil fertility, the practice of green manures as contribu-tions of major elements (N, P, and K) would be desirable along with studied crop rotations. The results showed that lands in the north-western foothills of Dahra are naturally intended for agriculture and predisposed to promot-ing agro-ecological practices, particularly agroforestry. This will improve soil health through enhanced biodiversity and efficient resource use. Also, the biological fertility measures offer more opportunities for sustainable agriculture in semi-arid environments where agroforestry practic-es and green manures effectively contribute to increasing organic matter content, bio-fertility, income diversity, and the standard of living for farmers.